A Low-cost Soft Tactile Sensing Array Using 3D Hall Sensors. (2016) - Wang, Hongbo; de Boer, Greg; Kow, Junwai; Ghajari, Mazdak; Alazmani, Ali; Hewson, Robert; Culmer, Peter
Abstract: Tactile sensors are essential for robotic systems to safely interact with the external world and to precisely manipulate objects. Existing tactile sensors are typically either expensive or limited by poor performance, and most are not mechanically compliant. This work presents MagTrix, a soft tactile sensor array based on four 3D Hall sensors with corresponding permanent magnets. MagTrix has the capability to precisely measure triaxis force (1 mN resolution) and to determine contact area. In summary, the presented tactile sensor is robust, low-cost, high-performance and easily customizable to be integrated into a range of robotic and healthcare applications.